(untitled) (Mumbai, 2002)
The DNA programming model, the limitations of COM. Limitations of VB6 for DNA application development. Limitations of DNA internet development. The need to abstract th operating system...
Keywords: BASIC (ngôn ngữ chương trình máy tính),BASIC (Computer program language)